2004
DOI: 10.1007/s10267-004-0170-3
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic placement of Marasmiellus juniperinus

Abstract: Recent collections and the type specimen of Marasmiellus juniperinus, the type species of the genus, were examined. Phylogenetic placement, based on ribosomal large subunit (LSU) and internally transcribed spacer (ITS) sequences, is within the lentinuloid clade, nested among Gymnopus taxa. This placement dictates genus name usage and phylogenetic position of other putative species of Marasmiellus. The mating system is tetrapolar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Androsacei), more species (reliably identified) and more DNA sequences should be included in analyses. Our gymnopoid clade also includes Marasmiellus and Rhodocollybia species, which is in accordance with results of Moncalvo et al (2002), Mata et al (2004) & Desjardin (2005). All these results indicate that Gymnopus and Marasmiellus (as conceived recently) are polyphyletic and that new taxonomic concepts inferred from DNA sequences should be proposed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Androsacei), more species (reliably identified) and more DNA sequences should be included in analyses. Our gymnopoid clade also includes Marasmiellus and Rhodocollybia species, which is in accordance with results of Moncalvo et al (2002), Mata et al (2004) & Desjardin (2005). All these results indicate that Gymnopus and Marasmiellus (as conceived recently) are polyphyletic and that new taxonomic concepts inferred from DNA sequences should be proposed.…”
Section: Discussionsupporting
confidence: 90%
“…On the basis of its non-hymeniform pileipellis, Antonín (1987) excluded members of the section Androsacei from Marasmius, and described a new genus Setulipes. Molecular phylogenetic studies published by Moncalvo et al (2002), Mata et al (2004) and Wilson & Desjardin (2005) showed that the type species of the genus Setulipes, S. androsaceus (L.) Antonín, belongs to the gymnopoid clade. Therefore, Noordeloos & Antonín (2008) transferred section Androsacei to the genus Gymnopus.…”
Section: Introductionmentioning
confidence: 99%
“…perforans formed a long branch of its own outside of /lentinuloid but within /omphalotaceae. Likewise, Mata et al (2004) based on nrLSU sequences, found that M. foetidum was placed within a clade dominated by Gymnopus taxa. The first study including both Mi.…”
Section: Introductionmentioning
confidence: 99%
“…and Lentinula. Mata et al (2004), based on an LSU analysis, also identified a clade containing sequences of M. foetidum and material named as Setulipes androsaceus (L.) Antonín and Gymnopus fusipes (Bull.) Gray, the type species of those respective genera.…”
Section: Introductionmentioning
confidence: 99%